2003
DOI: 10.1097/00004032-200305000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Dose Reduction in Invasive Cardiology by Restriction to Adequate Instead of Optimized Picture Quality

Abstract: In this study, the cinegraphic image intensifier entrance dose level for coronary angiography was changed in four steps from dose level A (0.041 microGy frame(-1)), allowing high contrast, but coarse mottled background, to level D (0.164 microGy frame(-1)), affording high transparency and sharpness. Using this new approach throughout the course of 404 consecutive cardiac catheterizations, we reduced patient radiation exposures down to 11 to 16% of currently typical values: i.e., mean dose area products of 5.97… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 20 publications
1
28
0
4
Order By: Relevance
“…For example, substantial dose reduction (both E and scatter) can be achieved by making active use of collimation, and ensuring that the fluoroscopy and fluorography frame rates (as well as the detector entrance dose rates in these modes) are as low as necessary for the clinical task [19,20]. Furthermore, scatter dose to the cardiologist can be significantly reduced through the use of appropriate personal protective equipment, as well as table-, floor-and ceiling-mounted operator shielding.…”
Section: Radiation Use Optimisation In Cardiac Angiographymentioning
confidence: 99%
“…For example, substantial dose reduction (both E and scatter) can be achieved by making active use of collimation, and ensuring that the fluoroscopy and fluorography frame rates (as well as the detector entrance dose rates in these modes) are as low as necessary for the clinical task [19,20]. Furthermore, scatter dose to the cardiologist can be significantly reduced through the use of appropriate personal protective equipment, as well as table-, floor-and ceiling-mounted operator shielding.…”
Section: Radiation Use Optimisation In Cardiac Angiographymentioning
confidence: 99%
“…However, an interventionalist, experienced in radiation-reducing techniques, will vary image intensifier entrance dose levels in accordance with tube angulation, the documented structure and, not least, body mass index. With the exception of cases with special requirements, lower dose levels typically guarantee an adequate image quality [29].…”
Section: Tabellementioning
confidence: 99%
“…minimising the X-ray dose to the patient while preserving the quality of treatment), the use of low fluoroscopy pulse rate, image intensifier field size and collimation are recommended [1,12,13]. However, the studies that concluded that there was an impact on dose of some technical parameters had mostly used descriptive or univariate analyses and/or were carried out on a phantom [2,4,14,15]. Few studies have used multivariate methods to analyse the dose variation on patients' skin [13,16].…”
mentioning
confidence: 99%